2002
DOI: 10.1111/j.1875-595x.2002.tb00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of United States and Korean dental hygiene students using the Hiroshima University-Dental Behavioural Inventory (HU-DBI)

Abstract: There were considerable differences in dental health attitudes/behaviour among dental hygiene students in the two countries. The variation in the favourable attitudes/behaviour toward oral health appeared to reflect the students' clinical training experience in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 10 publications
3
68
1
2
Order By: Relevance
“…The HU-DBI has good test-retest reliability, and thus it is not only useful for understanding patients, but also predicting clinical outcomes (2,3). On the other hand, by using this test, the oral health behaviors were found to be very different between countries due to the difference in the health education systems (1,4,5) and differences between the cultures (6,7). Moreover, the studies showed that oral health behavior and attitudes improve by the level of education (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HU-DBI has good test-retest reliability, and thus it is not only useful for understanding patients, but also predicting clinical outcomes (2,3). On the other hand, by using this test, the oral health behaviors were found to be very different between countries due to the difference in the health education systems (1,4,5) and differences between the cultures (6,7). Moreover, the studies showed that oral health behavior and attitudes improve by the level of education (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Through their undergraduate study, it is logical that students in the field of dentistry develop and modify their behavior/attitudes towards their own health. This, in turn, could affect the oral health of their patients (1).…”
Section: Introductionmentioning
confidence: 99%
“…(Table 3- Globally, there has been an increase in awareness of Orthodontics as a dental specialty in children as well as adults [1][2]. The level of dental health knowledge, positive dental health attitude, and dental health behavior are interlinked and associated with the level of education and income as demonstrated by various studies [3][4][5][6][7][8]. Attitudes and perceptions towards dental appearance differ among populations and among individuals [9,10].…”
Section: Results:-mentioning
confidence: 99%
“…This questionnaire was developed in 1987 by Kawamura 9 . The HU-DBI showed good test-retest reliability by coefficient of 0.73 in 517 students over a four-week period 10 . The English version of the HU-DBI also had good test-retest reliability and translated validity in a sample of 26 bilinguists 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Oral health attitudes and behaviour among medical and dental students in Tehran, Iran HU-DBI questionnaire has been administered in many countries such as UK, 9 USA, 10 South Korea, 11 China, 12 Yemen, 13 Greece, 14 Romania, 15 Turkey, 16 India 17,18 and Jordan. 19 Thus, it can provide the possibility of comparison among various countries, and to assess cross-cultural differences.…”
Section: Introductionmentioning
confidence: 99%